The Right Ventricular Diameter can Predict the Presence of Pulmonary Hypertension (Bangladesh Heart Journal, 2016)
Background: Pulmonary arterial hypertension (PAH) is a severe disease characterized by a progressive increase of pulmonary pressure and resistance leading to right heart failure. Pulmonary arterial hypertension is commonly diagnosed at a late stage of the disease and is associated with progressive clinical deterioration and premature death. The assessment of pulmonary artery pressure is important in clinical management and prognostic evaluation of patients with cardiovascular and pulmonary disease. Although PH can be detected invasively by right ventricular (RV) catheterization, accurate non-invasive assessment by echocardiography has many advantages. Reliable non-invasive evaluation of pulmonary pressure at present is still a problem as echocardiographic measurement of pulmonary hypertension relies on the presence of tricuspid regurgitation (TR). Objective: The purpose of this study was to determine whether right ventricular end diastolic diameter can predict the presence of pulmonary hypertension. Methods: Eighty consecutive patients with echo detectable tricuspid regurgitation who underwent right heart catheterization for either diagnostic or therapeutic procedure were recruited. They were divided into two groups on the basis of pulmonary artery systolic pressure (PASP). Group I consists of 40 patients with PASP >35 mm Hg and Group II 40 patients having PASP d 35 mm Hg. Right ventricular end-diastolic diameter (RVD) was measured in the apical 4 chamber view. PASP was measured from right heart catheterization. Results: The RVD has strong correlation with catheter-derived PASP, at a cutoff value of >3 cm, predicted the presence of PAH with 78% sensitivity and 71% specificity. Conclusion: RVD is a good non-invasive predictor for PAH. RVD can predict the presence of PAH even in absence of TR and correlates well with PASP measured by RV catheterization.Bangladesh Heart Journal 2015; 30(2) : 48-52